TELAAH PENGGUNAAN SKALA SIKAP DALAM PENILAIAN DENGAN PERBANDINGAN DUA MODEL SKALA (DENGAN MODEL CONTOH PENILAIAN SILA) - Hesti Sadtyadi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2018)
This study aims to determine the advantages of using two types of scale models by comparing Likert scale and semantics differential scale, in addition to knowing the silla construct and knowing the indicators. This study uses a development model, using the Borg and Gall model, which is adjusted. The sample used was the Buddhist community in the Central Java region, which consisted of Wonogiri, Semarang and Temanggung Regencies. Analysis by using factor analysis with exploratory factor analysis, in addition to descriptive analysis. The results of the study show that the components that can be used to compile the Silla instruments in Buddhism, according to the two instruments, consist of five dimensions of the Buddhist Pancasila. The indicators in each component of the Silla include four indicators of silla, namely thoughts, speech, physical body actions, and self-control. The advantages and disadvantages of the two forms of attitude rating scale, are differential semantic scales, have more advantages in terms of relatively higher validity and reliability.